Adapting English Language Teaching to 21st Century Learners Through Kahoot Application - Tiofanny Elisabet Sirait; Tiondina Samosir; Tri Inda; Lihardo Manik; Dumaris E Silalahi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study explores the use of the Kahoot! application as a digital learning tool to enhance motivation, cooperation, and comprehension among vocational high school students in English language teaching. As 21st-century learners, students today are digital natives who require interactive and technology-based learning environments. The research was conducted at SMK Swasta HKBP Pematang Siantar using a qualitative descriptive approach. Data were collected through classroom observation, documentation, and field notes. The results showed that Kahoot! significantly increased students’ enthusiasm, participation, and teamwork during English lessons. Students were more focused, cooperative, and motivated when learning through game-based quizzes. Moreover, repeated quiz activities improved their understanding of lesson materials through active recall and feedback. Despite some technical challenges such as limited internet access and shared devices, the overall learning atmosphere became more dynamic, joyful, and engaging. The study concludes that integrating Kahoot! into English teaching effectively supports interactive, fun, and student-centered learning for digital-age learners. Keyword : Kahoot! Application,English language teaching,Digital natives,Motivation,Game-based learning